Estimation of Price Elasticities from Norwegian Household Survey Data - Leif Brubakk (Statistics Norway, Research Department, 1997)
In this paper, a subsystem of demand equations is estimated using data from the Norwegian survey of household expenditures 1989-1991. One objective has been to obtain substantial knowledge of Norwegian household demand for a set of food groups, with emphasis on price responses, using two different approaches, namely, the method proposed in Deaton (1990), which utilises unit values instead of market prices, and an alternative approach, which relies on market prices. Comparing the two approaches, we conclude that they produce significantly different results. Possible explanations of this finding and implications for further research are discussed.
Keywords: C3; C5; D1; 330; Consumer demand; price elasticities; unit values; quality.